When disruption strikes the curriculum: Towards a crisis-curriculum analysis framework. (3rd June 2021) - Govender, Lynelle; de Villiers, Marietjie R.
Abstract: Introduction: COVID-19 has severely disrupted health professions training globally. This pandemic has been preceded by several other interferences on a smaller scale, setting the scene for crises in perpetuity. With a reactive stance adopted, these crises may result in rapid shifts to curricula, minimizing the opportunity for thorough planning and critical analyses. Guidance from the literature: Recognizing the limited frameworks available to provide structure to such curricular crises responses, we drew on the literature to develop a crisis-curriculum analysis framework. The work of the SPICES model by Harden et al., the four-dimensional framework by Steketee et al., and Deverell's crisis-induced learning, was used to develop the framework. Crisis-curriculum analysis framework: The framework provides a structured approach to curriculum analysis in the face of disruption. It is designed to meet the needs of the global health professions education community, currently in the midst of a crisis. Accompanied by a step-wise guideline, this framework is suitable for educators requiring a practically-orientated approach to curriculum analysis. Conclusion: Recognizing that curriculum analysis is but one part of crisis-management, we argue that this crisis-curriculum analysis framework may align well with strengthening institutional readiness as educators seek to refine and entrench curricular practices adopted during COVID-19.